A corrosion-resistant electrical shielding cabinet

By adopting a laminated shielding layer structure in the electrical shielding cabinet, combining a polycarbonate protective layer and a porous epoxy resin composite film layer, containing carbon nanotubes and silver nanowires, the existing electromagnetic shielding materials are solved. The problem is that more efficient electromagnetic shielding effect and corrosion resistance of the material are achieved.

CN119072104BActive Publication Date: 2025-02-18ZHEJIANG GREEN IDEAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411545232.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-18
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The electromagnetic shielding performance of existing electromagnetic shielding materials is insufficient, and their ease of processability and corrosion resistance need to be improved.

Method used

Using a laminated shielding layer structure, including a composite film layer formed by polycarbonate type protective layer and a porous epoxy resin, carbon nanotubes and silver nanowires are distributed in the composite film layer, and capsules are formed by epoxy resin coated with sodium bicarbonate. To improve the pore distribution and electromagnetic shielding performance of the membrane body.

Benefits of technology

It significantly improves electromagnetic shielding performance, while maintaining the easy processability and corrosion resistance of the material, and is suitable for applications such as electrical control cabinets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a corrosion-resistant electrical shielding cabinet, comprising a cabinet body and a shielding layer arranged on the cabinet body. In this scheme, the shielding layer is composed of a laminated configuration of protective layer / composite film layer / protective layer. The polycarbonate protective layer has many advantages such as aging resistance and high strength, and can protect the composite film layer. The composite film layer uses a porous epoxy resin as a film body, and the porous configuration cooperates with carbon nanotubes, silver nanowires, etc. in the film body to help further enhance the electromagnetic shielding function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrical cabinet devices, and in particular to a corrosion-resistant electrical shielding cabinet. Background Art

[0002] There are many electronic devices installed in the electrical control cabinet. In order to prevent the external electromagnetic radiation from affecting the operation of the equipment, the material of the cabinet must generally have electromagnetic shielding properties, such as lead alloy. However, this type of metal has defects such as heavy weight, difficult to move, and high difficulty in processing and molding. Composite shielding materials formed by polymer-coated fillers have become a research hotspot due to their advantages such as easy processing and light weight. Common examples include coated fiber filaments and nanowires, but the disadvantage is that the electromagnetic shielding performance is insufficient and needs to be improved. Summary of the invention

[0003] To solve at least one of the above technical defects, the present invention provides the following technical solutions:

[0004] The present application document discloses a corrosion-resistant electrical shielding cabinet, comprising a cabinet body and a shielding layer arranged on the cabinet body, wherein the shielding layer comprises a protective layer on the top surface and the bottom surface and at least one composite film layer between the protective layers, wherein the protective layer is a polycarbonate type, and the composite film layer is formed of a porous epoxy resin film body and carbon nanotubes and silver nanowires are distributed in the film body.

[0005] In this scheme, the shielding layer is composed of a laminated configuration of protective layer / composite film layer / protective layer. The polycarbonate protective layer has many advantages such as aging resistance and high strength, and can protect the composite film layer. The composite film layer uses porous epoxy resin as the film body. The porous configuration, combined with carbon nanotubes, silver nanowires, etc. in the film body, helps to further enhance the electromagnetic shielding function.

[0006] Furthermore, based on mass, polycarbonate, antioxidant 168, antioxidant 1076, and antioxidant 1010 are mixed and extruded into granules in a ratio of 100:0.1-0.2:0.2-0.4:0.2-0.3, and then injection molded into a plate body, i.e., a protective layer. The compound antioxidant in this solution helps to improve the hydrolysis resistance.

[0007] Further, the temperature of each extrusion zone is set as follows: 180-210℃, 260-275℃, 250-265℃, 260-275℃, 220-240℃, 220-240℃, 210-220℃, 210-220℃, 210-220℃, 235-245℃.

[0008] Furthermore, the carbon nanotubes are dispersed in an epoxy resin solution and dripped into the silver nanowire dispersion by a dripping method to form a spherical composite;

[0009] Sodium bicarbonate is coated with epoxy resin to form capsules, and the capsules are mixed with the spherical composite body and injection molded into a composite film layer;

[0010] The protective layer and the composite film layer are stacked and hot pressed to form a shielding layer.

[0011] In this scheme, epoxy resin is used to coat sodium bicarbonate to form capsules. During the process of mixed injection molding of the capsules and the spherical composite, the sodium bicarbonate reacts to distribute a number of pores in the formed film. The pores in the film, in combination with carbon nanotubes and silver nanowires, can further improve the electromagnetic shielding performance.

[0012] Furthermore, the carbon nanotubes account for 0.01-0.05% of the mass of the epoxy resin solution, and the concentration of the silver nanowire dispersion is 1-5 mg / ml.

[0013] Furthermore, the mass ratio of the capsule to the spherical complex is 1:7-10, and under the limited ratio, the electromagnetic shielding performance and the structural strength are at a predetermined balance point.

[0014] Furthermore, sodium bicarbonate, sodium dodecylbenzenesulfonate and triethylenetetramine are placed in an alcohol solution of the epoxy resin, the temperature is raised to react, and the reaction product obtained by solid-liquid separation is mixed with petroleum ether and an epoxy resin promoter and continuously stirred. The particles after solid-liquid separation are washed and dried, i.e., capsules. The epoxy resin is initially coated with sodium bicarbonate and then modified with a promoter for a second time, which helps to further improve the coverage rate of the epoxy resin, shorten the decomposition temperature range in the subsequent film, and make the pore distribution in the subsequent film more uniform.

[0015] Furthermore, the concentration of the epoxy resin in the alcohol solution is 0.6-1.2 g / ml, and the mass ratio of the sodium bicarbonate to the epoxy resin in the alcohol solution is 3-6:1.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention installs a laminated shielding layer on the cabinet body, and uses a polycarbonate protective layer to protect the composite film layer in the middle. The porous film body in the composite film layer cooperates with carbon nanotubes and silver nanowires to help improve the electromagnetic shielding function. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with specific embodiments.

[0019] Example 1

[0020] A corrosion-resistant electrical shielding cabinet comprises a cabinet body and a shielding layer installed on the peripheral wall of the cabinet body, wherein the shielding layer comprises a protective layer on the top surface and the bottom surface and a composite film layer between the protective layers.

[0021] The protective layer is of polycarbonate type, and the preparation process is as follows: polycarbonate (PC02-10), antioxidant 168, antioxidant 1076, and antioxidant 1010 are mixed in a ratio of 100:0.1:0.3:0.2 by mass, and stirred at high speed for 20 minutes. The evenly mixed material is poured into an extruder for granulation. The temperature settings of each zone of the extruder are as follows: 200°C, 265°C, 255°C, 270°C, 230°C, 230°C, 210°C, 215°C, 215°C, 235°C, the screw speed is 280r / min, and the feeding rate is 60kg / h.

[0022] The prepared master batch was placed in an oven at 100°C for 3 hours and the dried master batch was added into an injection molding machine and injection molded into a plate with a thickness of 2 mm, i.e., a protective layer.

[0023] The composite membrane layer is formed of a porous epoxy resin and carbon nanotubes and silver nanowires are distributed in the membrane. The preparation process is as follows:

[0024] Dissolve bisphenol A epoxy resin in acetone solvent, add 0.015% of carboxylated carbon nanotubes (aspect ratio of 90-100) based on the mass of bisphenol A epoxy resin, 0.01% of polyethylene glycol octylphenyl ether based on the mass of bisphenol A epoxy resin, and 10% of modified imidazole latent curing agent based on the mass of bisphenol A epoxy resin, stir for 10 minutes, and ultrasonically disperse for 1 hour for standby use.

[0025] A polyvinyl pyrrolidone dispersant accounting for 3% of the mass of bisphenol A epoxy resin is dissolved in deionized water to form a 0.003g / ml solution, and then silver nanowires are added to the solution to form a 3.0mg / ml mixed solution. The mixed solution is placed in a container and stirred, and the prepared bisphenol A epoxy resin solution is dropped into the stirred mixed solution. The formed spheres are filtered out, repeatedly washed and dried, and the obtained spheres are carbon nanotube / silver nanowire composites with a particle size of 100-200μm.

[0026] Sodium bicarbonate (180-200 mesh), sodium dodecylbenzene sulfonate, and triethylenetetramine are placed in an isopropanol solution (1%) of bisphenol A epoxy resin and stirred continuously for 20 minutes. The mass ratio of sodium bicarbonate, sodium dodecylbenzene sulfonate, triethylenetetramine and bisphenol A epoxy resin is 4:0.1:0.1:1. Heat to 70°C and react for 5 hours. During the reaction, the sodium bicarbonate is coated with epoxy resin to form capsules. Filter and mix the filter cake with petroleum ether and accelerator (DMP-30). Stir continuously for 3 hours. The mass ratio of petroleum ether, accelerator and bisphenol A epoxy resin is 80:0.2:1. Then filter and filter out the product and wash it. After washing, the product is dried at 50°C for 24 hours to obtain the desired capsules.

[0027] The capsules and the carbon nanotube / silver nanowire composite were mixed in a mass ratio of 1:8 and injection molded into a composite film layer, and the thickness of the composite film layer was 1.2 mm.

[0028] The layers are stacked in the configuration of protective layer / composite film layer / protective layer, and the shielding layer is formed by heat pressing.

[0029] Example 2

[0030] A corrosion-resistant electrical shielding cabinet comprises a cabinet body and a shielding layer installed on the peripheral wall of the cabinet body, wherein the shielding layer comprises a protective layer on the top surface and the bottom surface and a composite film layer between the protective layers.

[0031] The protective layer is of polycarbonate type, and the preparation process is as follows: polycarbonate (PC02-10), antioxidant 168, antioxidant 1076, and antioxidant 1010 are mixed in a ratio of 100:0.2:0.2:0.3 by mass, and stirred at high speed for 20 minutes. The evenly mixed material is poured into an extruder for granulation. The temperature settings of each zone of the extruder are as follows: 205°C, 270°C, 260°C, 265°C, 235°C, 235°C, 215°C, 215°C, 215°C, 240°C, the screw speed is 300r / min, and the feeding rate is 60kg / h.

[0032] The prepared master batch was placed in an oven at 120° C. and dried for 3 h. The dried master batch was added into an injection molding machine and injection molded into a plate with a thickness of 2 mm, i.e., a protective layer.

[0033] The composite membrane layer is formed of a porous epoxy resin and carbon nanotubes and silver nanowires are distributed in the membrane. The preparation process is as follows:

[0034] Dissolve bisphenol A epoxy resin in acetone solvent, add 0.025% of carboxylated carbon nanotubes (aspect ratio of 90-100) based on the mass of bisphenol A epoxy resin, 0.01% of polyethylene glycol octylphenyl ether based on the mass of bisphenol A epoxy resin, and 10% of modified imidazole latent curing agent based on the mass of bisphenol A epoxy resin, stir for 10 minutes, and ultrasonically disperse for 1 hour for standby use.

[0035] A polyvinyl pyrrolidone dispersant accounting for 3% of the mass of bisphenol A epoxy resin is dissolved in deionized water to form a 0.003g / ml solution, and then silver nanowires are added to the solution to form a 3.0mg / ml mixed solution. The mixed solution is placed in a container and stirred, and the prepared bisphenol A epoxy resin solution is dropped into the stirred mixed solution. The formed spheres are filtered out, repeatedly washed and dried, and the obtained spheres are carbon nanotube / silver nanowire composites with a particle size of 100-200μm.

[0036] Sodium bicarbonate (180-200 mesh), sodium dodecylbenzene sulfonate, and triethylenetetramine are placed in an isopropanol solution (1.5%) of bisphenol A epoxy resin and stirred continuously for 20 minutes. The mass ratio of sodium bicarbonate, sodium dodecylbenzene sulfonate, triethylenetetramine and bisphenol A epoxy resin is 5:0.2:0.1:1. Heat to 75°C and react continuously for 5 hours. During the reaction, the sodium bicarbonate is coated with epoxy resin to form capsules. Filter and mix the filter cake with petroleum ether and accelerator (DMP-30). Stir continuously for 3 hours. The mass ratio of petroleum ether, accelerator and bisphenol A epoxy resin is 85:0.2:1. Then filter and filter out the product and wash it. After washing, the product is dried at 50°C for 24 hours to obtain the desired capsules.

[0037] The capsules and the carbon nanotube / silver nanowire composite were mixed in a mass ratio of 1:9 and injection molded into a composite film layer, and the thickness of the composite film layer was 1.2 mm.

[0038] The layers are stacked in the configuration of protective layer / composite film layer / protective layer, and the shielding layer is formed by heat pressing.

[0039] Example 3

[0040] A corrosion-resistant electrical shielding cabinet comprises a cabinet body and a shielding layer installed on the peripheral wall of the cabinet body, wherein the shielding layer comprises a protective layer on the top surface and the bottom surface and a composite film layer between the protective layers.

[0041] The protective layer is of polycarbonate type, and the preparation process is as follows: by mass, polycarbonate (PC02-10), antioxidant 168, antioxidant 1076, and antioxidant 1010 are mixed in a ratio of 100:0.15:0.4:0.25, and stirred at high speed for 20 minutes. The evenly mixed material is poured into an extruder for granulation. The temperature settings of each zone of the extruder are as follows: 190°C, 260°C, 260°C, 270°C, 230°C, 230°C, 210°C, 210°C, 210°C, 240°C, the screw speed is 310r / min, and the feeding rate is 60kg / h.

[0042] The prepared master batch was placed in an oven at 110° C. and dried for 3 h. The dried master batch was added into an injection molding machine and injection molded into a plate with a thickness of 2 mm, i.e., a protective layer.

[0043] The composite membrane layer is formed of a porous epoxy resin and carbon nanotubes and silver nanowires are distributed in the membrane. The preparation process is as follows:

[0044] Dissolve bisphenol A epoxy resin in acetone solvent, add 0.02% of carboxylated carbon nanotubes (aspect ratio of 90-100) based on the mass of bisphenol A epoxy resin, 0.01% of polyethylene glycol octylphenyl ether based on the mass of bisphenol A epoxy resin, and 10% of modified imidazole latent curing agent based on the mass of bisphenol A epoxy resin, stir for 10 minutes, and ultrasonically disperse for 1 hour for standby use.

[0045] A polyvinyl pyrrolidone dispersant accounting for 3% of the mass of bisphenol A epoxy resin is dissolved in deionized water to form a 0.003g / ml solution, and then silver nanowires are added to the solution to form a 3.0mg / ml mixed solution. The mixed solution is placed in a container and stirred, and the prepared bisphenol A epoxy resin solution is dropped into the stirred mixed solution. The formed spheres are filtered out, repeatedly washed and dried, and the obtained spheres are carbon nanotube / silver nanowire composites with a particle size of 100-200μm.

[0046] Sodium bicarbonate (180-200 mesh), sodium dodecylbenzene sulfonate, and triethylenetetramine are placed in an isopropanol solution (1%) of bisphenol A epoxy resin and stirred continuously for 20 minutes. The mass ratio of sodium bicarbonate, sodium dodecylbenzene sulfonate, triethylenetetramine and bisphenol A epoxy resin is 5:0.1:0.2:1. Heat to 70°C and react continuously for 6 hours. During the reaction, the epoxy resin is used to coat the sodium bicarbonate to form capsules. Filter and mix the filter cake with petroleum ether and accelerator (DMP-30). Stir continuously for 4 hours. The mass ratio of petroleum ether, accelerator and bisphenol A epoxy resin is 80:0.2:1.1. Then filter and filter out the product and wash it. After washing, the product is dried at 50°C for 24 hours to obtain the desired capsules.

[0047] The capsules and the carbon nanotube / silver nanowire composite were mixed in a mass ratio of 1:7 and injection molded into a composite film layer, and the thickness of the composite film layer was 1.2 mm.

[0048] The layers are stacked in the configuration of protective layer / composite film layer / protective layer, and the shielding layer is formed by heat pressing.

[0049] Comparative Example 1

[0050] Compared with Example 3, no sodium bicarbonate was added in this example, and the capsule was replaced by epoxy resin of equal mass.

[0051] Comparative Example 2

[0052] Compared with Example 3, there is no step of coating sodium bicarbonate with epoxy resin to form capsules in this example, and equal weights of sodium bicarbonate, epoxy resin and spherical composite are mixed.

[0053] Comparative Example 3

[0054] Compared with Example 3, in this example, no antioxidant 168 is added, and the ratio of the total amount of antioxidant to polycarbonate remains unchanged.

[0055] The electromagnetic shielding performance of the shielding layer prepared above was tested in a frequency range of 12 to 18 GHz, as shown in Table 1:

[0056] Table 1

[0057]

[0058] When sodium bicarbonate is coated with epoxy resin, the decomposition temperature is increased and the distribution of pores in the film is more uniform. In comparison, in Example 2, sodium bicarbonate is completely decomposed at a lower temperature, and the pores in the subsequently formed film are not obvious. There is a difference in electromagnetic shielding performance between the two.

[0059] In the wet heat aging test, it was found that the hydrolysis resistance of the protective layer in Comparative Example 3 was much lower than that of the protective layers in the examples.

[0060] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A corrosion-resistant electrical shielding cabinet, comprising a cabinet body and a shielding layer arranged on the cabinet body, characterized in that: The shielding layer includes a protective layer on the top surface, a protective layer on the bottom surface and at least one composite film layer between the protective layers, the protective layer is a polycarbonate type, the composite film layer is formed of a porous epoxy resin film body and carbon nanotubes and silver nanowires are distributed in the film body; The carbon nanotubes are dispersed in an epoxy resin solution and dripped into a silver nanowire dispersion to form a spherical composite; Sodium bicarbonate is coated with epoxy resin to form capsules, and the capsules are mixed with the spherical composite body and injection molded into a composite film layer; The protective layer and the composite film layer are stacked and hot pressed to form a shielding layer; The mass ratio of the capsule to the spherical complex is 1:7-10; Sodium bicarbonate, sodium dodecylbenzenesulfonate and triethylenetetramine are placed in an alcohol solution of epoxy resin, the temperature is raised for reaction, and the reaction product obtained by solid-liquid separation is mixed with petroleum ether and epoxy resin accelerator and continuously stirred. The particles after solid-liquid separation are washed and dried to obtain capsules.

2. A corrosion-resistant electrical shielding cabinet as claimed in claim 1, characterized in that: Based on mass, polycarbonate, antioxidant 168, antioxidant 1076, and antioxidant 1010 are mixed in a ratio of 100:0.1-0.2:0.2-0.4:0.2-0.3 and extruded into granules, and then injection molded into a plate body, i.e., a protective layer.

3. A corrosion-resistant electrical shielding cabinet as claimed in claim 2, characterized in that: The temperature settings of each extrusion zone are as follows: 180-210℃, 260-275℃, 250-265℃, 260-275℃, 220-240℃, 220-240℃, 210-220℃, 210-220℃, 210-220℃, 235-245℃.

4. The corrosion-resistant electrical shielding cabinet according to claim 1, characterized in that: The carbon nanotubes account for 0.01-0.05% of the mass of the epoxy resin solution, and the concentration of the silver nanowire dispersion is 1-5 mg / ml.

5. The corrosion-resistant electrical shielding cabinet according to claim 1, characterized in that: The concentration of the epoxy resin in the alcohol solution is 0.6-1.2 g / ml, and the mass ratio of the sodium bicarbonate to the epoxy resin in the alcohol solution is 3-6:1.

Citation Information

Patent Citations

  • Transparent conductive film and its manufacturing method

    JP2009070660A